Leadership In Electoral Politics Of Assam: The Role Of Tea Garden Community (Journal of Namibian Studies : History Politics Culture, 2022)
Leadership in the electoral politics of Assam is a complex and evolving phenomenon shaped by historical legacies, ethnic diversity, socio-economic challenges and shifting political alliances. The tea garden community's role in the electoral politics of Assam is both significant and evolving. Their large population, economic contribution, and growing political awareness make them a crucial demographic for any political party seeking power in Assam. The leadership emerging from within this community holds the potential to address historical injustices and work towards a more inclusive and prosperous future for the Tea Garden Labourers (TGLs) and their families. In this context, the present article will primarily address two issues: why and how the concept of leadership emerged among the Tea Garden Community in the political domain of Assam, and the role of trade unions, such as Assam Chah Mazdoor Sangha (ACMS), in developing leadership among the Tea Garden Community.